At risk - Cornwell, Patricia Daniels (New York : G. P. Putnam's Sons, 2006)
A Massachusetts district attorney running for governor wants to use some radical new DNA technology to solve a long-ago murder. The result? A new round of violence.
Keywords: Public prosecutors -- Massachusetts -- Fiction; Detective and mystery fiction